‘TO SPEAK OF CATTLE IS TO SPEAK OF MAN’: ANTHROPARCHAL INTERACTIONS IN JOHN CONNELL’S “THE FARMER’S SON” - PARASCHIV, Paul Mihai (Studia Universitatis Babeș-Bolyai Philologia, 2021)
“To speak of cattle is to speak of man”: Anthroparchal Interactions in John Connell’s The Farmer’s Son. The present paper intends to build a critique of contemporary farming practices, based on Erika Cudworth’s theory of “anthroparchy.” By exemplifying how anthroparchal interactions function in John Connell’s memoir, I will outline the becoming of a posthuman farmer that awakens certain sensibilities towards nonhuman animals, in ways that compel a rethinking of gendered relations, patriarchy, violence, and capitalist interests. The analysis provides a needed insight into recent developments in Irish rural farming, detailing the position of the human subject in relation to nonhuman otherness and describing some of the changes that need to be made regarding the power relations that are at work within patriarchal systems. To this extent, Cudworth’s theoretical framework and Connell’s memoir are proven to be contributing to the necessary restructuring of farming practices and of human-nonhuman interactions. REZUMAT. „A vorbi despre bovine înseamnă a vorbi despre om”: Interacțiuni antroparhice în The Farmer’s Son de John Connell. Prezenta lucrare intenționează să construiască o critică a practicilor agricole contemporane, bazată pe teoria "antroparhiei" formulată de către Erika Cudworth. Exemplificând modul în care interacțiunile antroparhiale funcționează în memoriile lui John Connell, voi contura procesul de devenire a unui fermier postuman care reușește să trezească anumite sensibilități față de animalele nonumane, în moduri care ne obligă să regândim relațiile de gen, patriarhatul, violența și interesele capitaliste. Analiza oferă o perspectivă necesară asupra dezvoltărilor recente din agricultura rurală irlandeză, detaliind poziția subiectului uman în raport cu alteritatea nonumană și descriind unele dintre schimbările care trebuie făcute în ceea ce privește relațiile de putere care se desfășoară în cadrul sistemelor patriarhale. În această măsură, cadrul teoretic al lui Cudworth și memoriile lui Connell pot contribui la restructurarea necesară a practicilor agricole și a interacțiunilor uman-nonuman. Cuvinte-cheie: antroparhie, postumanism, relații de gen, zoomorfism, capitalism, agricultură